2018
DOI: 10.1002/jcb.26564
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of tributyltin‐induced alterations in cholesterol homeostasis and steroidogenesis in hamster testis: In vivo and in vitro studies

Abstract: Tributyltins (TBT) are ubiquitous and persistent environmental contaminants that disturb normal endocrine function including gonadal function in humans and marine organisms. TBT was administered through oral route to male Syrian hamsters at daily doses of 50, 100, and 150 ppm/kg for 65 days. Changes in testis morphology, immunohistochemistry of iNOS, 3β-HSD, and 17β-HSD, cholesterol transport receptor, nuclear receptors, and transcription factors were analyzed. TBT treatment affected each of these parameters t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Because cholesterol is the precursor for sex hormone production, we predicted that the reduction in intracellular cholesterol upon TBT exposure would reduce theca cell steroid hormone production. In support of this hypothesis, in vivo studies have demonstrated that TBT exposure inhibits steroidogenic enzymes' transcription, and reduces serum testosterone production in mouse (Kim et al 2008) and hamster (Kanimozhi et al 2018) testes. In these studies, however, intracellular cholesterol was not assessed.…”
Section: Tbt Alters Star But Not Steroid Productionmentioning
confidence: 88%
See 1 more Smart Citation
“…Because cholesterol is the precursor for sex hormone production, we predicted that the reduction in intracellular cholesterol upon TBT exposure would reduce theca cell steroid hormone production. In support of this hypothesis, in vivo studies have demonstrated that TBT exposure inhibits steroidogenic enzymes' transcription, and reduces serum testosterone production in mouse (Kim et al 2008) and hamster (Kanimozhi et al 2018) testes. In these studies, however, intracellular cholesterol was not assessed.…”
Section: Tbt Alters Star But Not Steroid Productionmentioning
confidence: 88%
“…Exposure to endocrine disrupting chemicals (EDCs) can impair fertility and ovarian cell function (Craig and Ziv-Gal 2018;Mlynarcikova et al 2014), specifically altering steroidogenesis in vitro (Romani et al 2013;Romani et al 2014) and in vivo (Li et al 2012;Melzer et al 2011). TBT's steroidogenic effects have been reported in Leydig cells and testis (Kanimozhi et al 2018;Kariyazono et al 2015;Mitra et al 2014;Nakajima et al 2005). However, TBT's effect on ovarian steroidogenic cells has been restricted to granulosa cells.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in the present study, TPT downregulated many steroidogenic gene expression such as Lhcgr , Scarb1 , Star , Cyp11a1 , Hsd3b1 , Cyp17a1 , and Hsd17b3 . A recent study using another organotin tributyltin also showed that the expression levels of SCARB1, CYP11A1, HSD3B1, CYP17A1, and HSD17B3 were downregulated in the adult male hamster testes after 65-day treatment ( Kanimozhi et al, 2017 ). Secondly, TPT directly inhibited steroidogenic enzyme activities.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Grote et al (32) , one animal receiving 15 mg TBT/kg body weight died, but no signs of general toxicity were observed. Regarding the male reproductive organs, most studies have shown no changes in testes weight among the groups treated with TBT over a wide range of doses (33,34,35,32,36,24,37) .…”
Section: )mentioning
confidence: 99%
“…Steroidogenic acutely regulated proteins (StAR) and other hamster steroidogenic enzymes (expressions of Cypscc, Hsd 3β1 and Cyp17α1) were studied by real-time PCR, which revealed significantly decreased mRNA expression of StAR, Cypscc, Hsd 3β1 and Cyp17α1, all involved in normal testicular function and steroidogenesis. Immunoblotting research showed that the expression of StAR, 3β-HSD, Cypscc, Hsd 3β1 and Cyp17α1 was also significantly down-regulated in hamsters treated with TBT in a dose-dependent manner compared to control (37) (Table 4).…”
Section: )mentioning
confidence: 99%